KARAKTERISTIK PERKAWINAN CAKO SEBAGAI SIMBOL IDENTITAS KULTURAL MASYARAKAT MANGGARAI - Fransiskus Bustan; Agustinus Mahur; Labu Djuli; John Bhae Bhae (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
This paper discusses the characteristics of cako marriage as the symbol of cultural identity for Manggarai society, as reflected in the meaning of the cako marriage, customary rules in the cako marriage, and the changes of social role and status in the cako marriage, in view of social anthropology which deals with the study of the relationship of culture and society. The materials are based on data collected through research which is descriptive in nature. The results of study show that the cako marriage refers to the form of marriage between a man of the elder offspring and a woman of the younger offspring. As the two families are of the same clan, the cako marriage is endogamy. Based on the customary rules of Manggarai society, the cako marriage is only permitted for a woman of the younger offspring of the third layer above. Due to the cako marriage, the social role and status change in some respect as the elder offspring acts as wife taker is known as anak wina in Manggarai language and the younger offspring acts as wife giver known as anak rona in Manggarai language. Being wife taker, the elder offspring holds lower power, or vice versa, being wife giver, the younger offspring holds higher power.